THE EFFECT OF ETHIDIUM BROMIDE MUTAGENESIS ON MORPHOLOGICAL CHARACTERISTICS AND PHYSIO - BIOCHEMICAL PERFORMANCES OF LACTIC ACID BACTERIA ISOLATED FROM TRADITIONALLY FERMENTED ETHIOPIAN COW MILK - SEWUNET ABERA; MELAKU ALEMU; AMEHA KEBEDE (International Journal of Pharma and Bio Sciences, 2016)
Mutagenesis has been used to generate highly productive and stress tolerant variants of microbes. In this study a random mutagenesis using a chemical mutagen, ethidium bromide, was carried out on Lactic Acid Bacteria (LAB) isolated from Ethiopian traditionally fermented cow milk. Twenty colonies of LAB were isolated and out of which two isolates (B6S01 and A6B08) with least mean pH scores were selected and characterized to genus level. After being mutagenized with four different concentrations of ethidium bromide (0.5, 1.0, 1.5 and 2.0 g.L-1), 80 survivors were selected and screened. Accordingly, four mutants with the least mean pH scores were selected and characterized. The two wild type isolates, (B6S01 and A6B08) with mean pH 4.50 ± 0.03 and 4.52 ± 0.02 respectively, were identified as Lactobacillus spp. and Lactococcus spp respectively. The mutagenesis affected the sugar fermentation pattern and acidification potential of the mutants. The mutant types MAS03 and MAB18 were now able to ferment arabinose and fructose, and galactose respectively. Lower mean pH values were associated with ethidium bromide at 0.5 g-1L and 1.5 gL-1 concentration significantly (p<0.01). However, ethidium bromide at 2.0 gL-1 concentration resulted the least pH value, 4.20 ± 0.03, on the mutant MAB37. The effectiveness of the mutagenesis was demonstrated by better acidification potential and unique array of sugar fermentation. Utilization of these identified mutants in dairy processing could reduce production cost and enhance productivity.